Sewerage inflow and infiltration in Universiti Malaysia Pahang (Gambang) - Liew, Pei Qi (2015)
There are several problems occurring during heavy rain which public infrastructure defects will allow unwanted water to enter the sewer system. The sewer pipe system that had cracked or broken causes the excess water from inflow and infiltration to enter the sewer system. This will affect the flow rate and flow capacity of wastewater inside the sewer pipe. The main purpose of this research is to study the inflow and infiltration in the sewerage system by collecting data from field runs in UMP area. Besides, it also studies the relationship of rainfall intensity with inflow and infiltration rate in the sewerage system and to detect whether there are any leakage present in the sewer lines studied which may affect the flow rate in the sewer. This study about sewerage inflow and infiltration in selected sewer in both dry and wet periods, which using the two area velocity flow-meters to measure the sewer flow rate and rainfall data is collected using a rain gauge to achieve the objectives of the research. Thus, the differences between the two periods of inflow and infiltration, and its relationship with rainfall can be clearly seen. This is done on selected sewer line connecting two manholes with no lateral branches in between at Universiti Malaysia Pahang (UMP) area. The result of the inflow and infiltration analysis are compared with the inflow and infiltration rate design limits prescribed in Malaysia Standard MS 1228:1991, previous case studies on inflow and infiltration that carried out in Skudai, Johor and inflow and infiltration estimation range that mention in Hammer & Hammer. The highest infiltration rate that obtained (19.71 liter/day/km/mm-dia) is within the range of design limits prescribed in MS 1228: 1991(50 liter/day/km/mm-dia.) as well as the estimation range that suggested by Hammer & Hammer (18-46 liter/day/km/mm-dia.).